The acceptability of alcohol intoxication management services to users: A mixed methods study. (26th November 2019) - Irving, Andy; Buykx, Penny; Amos, Yvette; Goodacre, Steve; Moore, Simon C.; O'Cathain, Alicia
Abstract: Introduction and Aims: Alcohol Intoxication Management Services (AIMS) provide basic care for intoxication and minor injuries, have been increasingly implemented in urban areas characterised by a large number of premises licensed for the sale and on‐site consumption of alcohol, with the goal of reducing alcohol's burden on emergency services, including referrals into hospital emergency departments. The acceptability of new health services to users is a key effectiveness outcome. The aim was to describe patient experiences when attending an AIMS and document the acceptability of AIMS to users. Design and Methods: A sequential mixed methods study was undertaken involving semi‐structured interviews with participants from four AIMS followed by a survey of users recruited from six AIMS. Results: Interviewees ( N = 19) were positive about the care they received in AIMS and appreciated the friendly, non‐judgemental atmosphere. Survey respondents rated their experience in AIMS positively (on a 0 to 10 Likert scale, mean = 9.34, SD = 1.38, n = 188). Frequently given reasons for attendance included drinking alcohol (57%) and minor injury (42%); 24% said they would have attended the emergency department had the AIMS not been available and 6% said they would have preferred to go to the emergency department; 31% indicated they would have felt unsafe without the AIMS. Discussion and Conclusions: AIMS are acceptable to users. AIMS are likely to address previously unmet demand for a safe space within the night‐time environment.